Winning shopping center designs the International Council of Shopping Centers ... International Design and Development Awards winners. - International Council of Shopping Centers (New York The Council, 1996)
Annual
Description based on: 1996.
Keywords: Shopping centers -- Awards -- Periodicals; Architecture, Modern -- 20th century -- Periodicals